2014
DOI: 10.4103/1305-7456.130637
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a skeletal Class II malocclusion using fixed functional appliance with miniplate anchorage

Abstract: Based on our literature search, we found that the use of miniplate anchorage with Forsus fatigue-resistance device (FRD) has not yet been reported. Therefore, the aim of the present case report was to present the treatment of a patient with skeletal Class II malocclusion with mandibular retrusion using Forsus FRD with miniplate anchorage. Fixed appliances with 0.022-inch slots were attached to the maxillary teeth and after 8 months of the leveling and alignment of the upper arch, 0.019 × 0.025-inch stainless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 14 publications
2
38
0
6
Order By: Relevance
“…6,[8][9][10]15 The methods previously described to prevent mandibular incisor protrusion, such as using negative-torqued mandibular incisor brackets, sectional arches, and mini screws, were found to be unsuccessful, although the use of miniscrews decreased the mandibular incisor protrusion. 15 In the present study, the mandibular incisors were surprisingly retruded and this finding was also noted by Celikoglu et al 16 This change might be useful in the treatment of Class II malocclusion with protruded mandibular incisors and with diastema. It is possible that the pressure of the maxillary incisors and lower lip caused this change.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…6,[8][9][10]15 The methods previously described to prevent mandibular incisor protrusion, such as using negative-torqued mandibular incisor brackets, sectional arches, and mini screws, were found to be unsuccessful, although the use of miniscrews decreased the mandibular incisor protrusion. 15 In the present study, the mandibular incisors were surprisingly retruded and this finding was also noted by Celikoglu et al 16 This change might be useful in the treatment of Class II malocclusion with protruded mandibular incisors and with diastema. It is possible that the pressure of the maxillary incisors and lower lip caused this change.…”
Section: Discussionsupporting
confidence: 70%
“…Previously, Celikoglu et al 16 showed this to be a successful option for the treatment of Class II malocclusion with mandibular retrusion. However, its effects were not extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,16 Studies have recently focused on eliminating these undesirable effects. [12][13][14] The effects of the Forsus FRD appliance on maxillary growth were investigated by SNA and Co-A measurements. In both groups, a significant decrease was found in the SNA angle.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] However, to our knowledge, no study has compared the skeletal, dentoalveolar, and soft tissue effects of miniplate anchored Forsus FRDs and conventional Forsus FRDs in the treatment of Class II malocclusion. The aim of this prospective study was to compare the skeletal, dentoalveolar and soft tissue effects of miniplate anchored Forsus FRDs and conventional Forsus FRDs in the treatment of Class II malocclusion.…”
Section: Introductionmentioning
confidence: 99%